2017
DOI: 10.1177/2150135117690109
|View full text |Cite
|
Sign up to set email alerts
|

“Chorea”: A Unique Presentation of Left Atrial Myxoma in a Pediatric Patient

Abstract: We report an unusual presentation of a large left atrial myxoma in an eight-year-old girl who presented with the sudden onset of chorea. This case illustrates the fact that the presentation of chorea in nonendemic areas for rheumatic fever should raise suspicion for a myxoma. The chorea resolved soon after removal of the myxoma, supporting the hypothesis of an immune-mediated mechanism, or manifestation of paraneoplastic syndrome secondary to the myxoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Just like Smith et al in their review of the literature [ 4 ], we found a sample of patients who had a myxoma diagnosis that initially presented as a PS [ 7 - 18 ]. Some articles suggest grouping PS by the nature of the symptoms they experience, whether they are arthritic, hematologic, neurologic, respiratory, gastrointestinal, or dermatologic.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like Smith et al in their review of the literature [ 4 ], we found a sample of patients who had a myxoma diagnosis that initially presented as a PS [ 7 - 18 ]. Some articles suggest grouping PS by the nature of the symptoms they experience, whether they are arthritic, hematologic, neurologic, respiratory, gastrointestinal, or dermatologic.…”
Section: Reviewmentioning
confidence: 99%
“…The relevance of all these reports relies on the fact that these manifestations resolved with myxoma excision, suggesting a relationship with the myxoma or indicating a possible association with it [ 4 , 7 ]. Limitations of our study include the fact that only articles in English and Spanish were included, that PS in the context of CM might be underreported, and that the sample of our review might not be representative of the true population.…”
Section: Reviewmentioning
confidence: 99%